A combined acoustic and optical instrument for industry managed fisheries studies - Underwood, M.; Sherlock, M.; Marouchos, A.; Cordell, J.; Kloser, Rudy; Oceans, T.; Flagship, A. (2015)
© 2015 IEEE.The design of an existing in-house scientific instrument was used as a basis to create a new model suitable for deployment onto a fishing industry vessel, with a reduced need for specialized technical support. Some of the planned developmental goals were met directly, whilst others resulted in intermediate problems that required remedial action in order to deliver the desired outcome. The developmental goals and outcomes are presented, along with the range of intermediate issues and the methods used to resolve them.